Phenotypic Resemblance to Neuropsychiatric Disorder and Altered mRNA Profiles in Cortex and Hippocampus Underlying IL15Rα Knockout - He, Yi; Yu, Yuxin; Li, Yanan; Duan, Weicheng; Sun, Zuoli; Yang, Jian; Kastin, Abba J.; Pan, Weihong; Zhang, Yan; Wang, Kang (Frontiers in Neuroscience, 2021)
Abstract Background: Previous studies of the functions of IL15Rα have been limited to immune activities and skeletal muscle development. Immunological factors have been identified as one of the multiple causes of psychosis, and neurological symptoms have been described in IL15Rα knockout mice. Seeking to explore possible mechanisms for this in the IL15Rα-/- mouse brain, we analyzed gene expression patterns in the cortex and hippocampus using the RNA-seq technique. Methods: IL15Rα knockout mice were generated and littermate wildtype mice were used as a control group. A Y-maze was used to assess behavior differences between the two groups. The cortex and hippocampus of 3-month-old male mice were prepared and RNA-seq and transcriptome analysis were performed by GSEA. Results: Compared with the wildtype group, IL15Rα knockout animals showed higher speed in the novel arm and more entrance frequency in the old arm in the Y-maze experiment. GSEA analysis indicated that 18 pathways were downregulated and 13 pathways upregulated in both cortex and hippocampus from the GO, KEGG and Hallmarks gene sets. The downregulated pathways formed three clusters: respiratory chain and electron transport, regulation of steroid process, and skeletal muscle development. Conclusions: IL15Rα knockout mice exhibit altered expression of multiple pathways, which could affect many functions of the brain. Lipid biosynthesis and metabolism in the central nervous system should be investigated to provide insights into the effect of IL15Rα on psychosis in this murine model.